Natural Polysaccharides and Their Derivates: A Promising Natural Adjuvant for Tumor Immunotherapy - Li, Ye; Wang, Xiaomin; Ma, Xiaoran; Liu, Cun; Wu, Jibiao; Sun, Changgang (Frontiers in Pharmacology, 2021)
The treatment process of tumor is advanced with the development of immunotherapy. In clinical experience, immunotherapy has achieved very significant results. However, the application of immunotherapy is limited by a variety of immune microenvironment. For a long time in the past, polysaccharides such as lentinan and Ganoderma lucidum glycopeptide have been used in clinic as adjuvant drugs to widely improve the immunity of the body. However, their mechanism in tumor immunotherapy has not been deeply discussed. Studies have shown that natural polysaccharides can stimulate innate immunity by activating upstream immune cells so as to regulate adaptive immune pathways such as T cells and improve the effect of immunotherapy, suggesting that polysaccharides also have a promising future in cancer therapy. This review systematically discusses that polysaccharides can directly or indirectly activate macrophages, dendritic cells, NK cells etc., binding to their surface receptors, inducing PI3K/Akt, MAPK, Notch and other pathways, promote their proliferation and differentiation, increasing the secretion of cytokines, and improve the state of immune suppression. These results provide relevant basis for guiding polysaccharide to be used as adjuvants of cancer immunotherapy.